Al-Wakalah: Landasan Syariah, Rukun Syarat, Jenis-Jenis, dan Aplikasi di Perbankan Syariah - Leviana Acnez; Ahmad Fathi Ihsan; Erikh Ernala Tarigan (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Al-wakalah is a key contract in Islamic jurisprudence (fiqh muamalah) that regulates the granting of power of attorney from one party to another to carry out certain matters permitted by Islamic law. This research uses a descriptive qualitative method with a literature review as the primary approach to elaborate on the definition, pillars, requirements, types, and application of the al-wakalah contract in the context of Islamic banking. Data were collected from various relevant literature, scientific journals, and official documents, then analyzed in depth through content review. The results show that the al-wakalah contract not only serves as a legitimate and sharia-compliant mechanism for delegation of authority, but also serves as a key instrument in the operation of various Islamic banking products and services such as Letters of Credit, fund transfers, investment management, collections, and Islamic insurance. The implementation of this contract provides convenience, security, and legal certainty for the parties, while also supporting the strengthening of a transparent Islamic financial system based on sharia principles.